Effect of One-Step and Multi-Steps Polishing System on Enamel Roughness - Cynthia Sumali; Adi Hidayat; Joko Kusnoto; Widijanto Sudhana (Faculty of Dentistry, Universitas Indonesia, 2013)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--> The final procedures of orthodontic treatment are bracket debonding and cleaning the remaining adhesive. Multi-step polishing system is the most common method used. The disadvantage of that system is long working time, because of the stages that should be done. Therefore, dental material manufacturer make an improvement to the system, to reduce several stages into one stage only. This new system is known as one-step polishing system. Objective: To compare the effect of one-step and multi-step polishing system on enamel roughness after orthodontic bracket debonding. Methods: Randomized control trial was conducted included twenty-eight maxillary premolar randomized into two polishing system; one-step OptraPol (Ivoclar, Vivadent) and multi-step AstroPol (Ivoclar, Vivadent). After bracket debonding, the remaining adhesive on each group was cleaned by subjective polishing system for ninety seconds using low speed handpiece. The enamel roughness was subjected to profilometer, registering two roughness parameters (Ra, Rz). Independent t-test was used to analyze the mean score of enamel roughness in each group. Results: There was no significant difference of enamel roughness between one-step and multi-step polishing system (p>0.005). Conclusion: One-step polishing system can produce a similar enamel roughness to multi-step polishing system after bracket debonding and adhesive cleaning. DOI: 10.14693/jdi.v19i3.136